Female-Authored Articles Are More Likely to Include Methods-Trained Authors - da Graca, Briget (Mayo Clin Proc Innov Qual Outcomes, 2019)
OBJECTIVE: Studies with authors trained in research methods are of higher quality than those without. We examined inclusion of authors with master's or doctoral degrees incorporating advanced research methods training on original research articles in high-impact journals, investigating differences between journals and by first-author sex. METHODS: Using all original research articles from 1 issue of The New England Journal of Medicine (NEJM), Journal of the American Medical Association (JAMA), Annals of Internal Medicine (Annals), and JAMA-Internal Medicine/Archives of Internal Medicine (Archives) every alternate month, February 1994 to October 2016, we assessed the prevalence of articles listing authors with master's/doctoral research degrees and its adjusted associations with time of publication, journal, and first-author sex via multivariable logistic regression models (accounting for number of authors, study type, specialty/topic, and continent and for interactions between journal and time of publication, study type, and continent). RESULTS: Of 3009 articles examined, 84.4% (n=2539) had authors listing research degrees. After adjustment, the prevalence of such articles increased from 1994 to 2016 (P<.001), but patterns differed among journals. Annals and NEJM increased to approximately100% by 2016; JAMA and Archives peaked around 2010 to 2011, then declined. Articles with female first authors were more likely to list authors with research degrees (adjusted odds ratio=1.66; 95% CI, 1.29-2.13; P<.001). CONCLUSION: The prevalence of original research articles listing authors trained in research methods in high-impact journals increased significantly but is now declining at some journals, with potential effects on quality. The greater prevalence among female first-authored articles suggests possible sex differences in structuring/crediting research teams or subconscious sex bias during review.